FIGURATIVE LANGUAGE: A KEY TO UNDERSTANDING IN TAYLOR SWIFT'S "ENCHANTED" LYRICS. - Yuli Rohmiyati; Citra Septianingsih; Siti Fauzah (J-Shelves of Indragiri (JSI), 2023)
One of the best literary forms is a song. Another crucial fact to be aware of is that a song is a small piece of rhyming music that contains the songwriter's fantasies, ideas, illusions, and messages for the listener. Figurative language is used in song lyrics to help the reader understand the messages being conveyed. Additionally, the purpose of the current study is to identify the figurative language used in Taylor Swift's song "Enchanted" lyrics. The authors employed a descriptive qualitative study approach that included metaphors (379%) and other literary devices such as alliteration ( 21,6%), hyperbole (16,2%), personification (13,5% ), simile (5,4%) and irony (5,4%). The use of figurative language as a non-literal or idiomatic form of expression could increase learners' vocabulary and improve their language's expressiveness and proximity to their feelings.